Literatur Review : Perbandingan Asupan Protein Hewani dan Protein Nabati pada Balita Stunting di Indonesia - Vivi Indah Purnamasari; Fatmalina Febry (Universitas Malahayati Lampung, 2023)
ABSTRACT Stunting is a condition in which children experience impaired growth as a result of chronic nutritional problems, namely lack of nutritional intake for a long time. This study aims to determine the comparison of intake of animal protein and vegetable protein in stunted toddlers. Literature review is conducted by searching, summarizing, and combining the core of several scientific sources that are accurate and valid from search databases such as Google Scholar and Garuda Portal. The literature searched for is limited from 2015 to 2022 with the keywords